Improving Data Quality in Mass-Gatherings Health Research. Issue 3 (9th March 2017) - Guy, Andrew; Prager, Ross; Turris, Sheila; Lund, Adam
Abstract: Mass gatherings attract large crowds and can strain the planning and health resources of the community, city, or nation hosting an event. Mass-Gatherings Health (MGH) is an evolving niche of prehospital care rooted in emergency medicine, emergency management, public health, and disaster medicine. To explore front-line issues related to data quality in the context of mass gatherings, the authors draw on five years of management experience with an online, mass-gathering event and patient registry, as well as clinical and operational experience amassed over several decades. Here the authors propose underlying human, environmental, and logistical factors that may contribute to poor data quality at mass gatherings, and make specific recommendations for improvement through pre-event planning, on-site actions, and post-event follow-up . The advancement of MGH research will rely on addressing factors that influence data quality and developing strategies to mitigate or enhance those factors. This is an exciting time for MGH research as higher order questions are beginning to be addressed; however, quality research must start from the ground up to ensure optimal primary data capture and quality. A Guy, R Prager, S Turris, A Lund .Improving data quality in mass-gatherings health research .Prehosp Disaster Med .2017 ;32 (3 ):329 –332 .